Results of examination of early melanoma detection carried out on citizens of Poznań - Kycler, Witold; Świerzewski, Adam; Teresiak, Marek; Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2006)
Incidence and mortality of melanoma in Poland and in other countries have risen steeply. Tumor depth remains the best predictor of patient survival. However, physical examination is still associated with an increase in the probability of detecting thinner melanomas. In many countries a number of cancer organizations have introduced screening or early detection programs of melanoma. Results of such studies are under debate. Recently The Great Poland Cancer Center and the Municipal Council of Poznań have carried out a campaign of early detection of melanomas. Invitation for participation in the study was announced by newspapers, the internet and radio. This study included 2006 patients who visited The Great Poland Cancer Center in 2002 during the whole 6 month campaign. There were two times more women than men. Total body skin examination was performed on all subjects, and surgical excision of a lesion was recommended in 599 (29.9%) cases. Melanoma was diagnosed in 8 cases (0.4%) and 40 cases (2%) of non melanoma skin cancers were found. The obtained results lead to the following conclusions: (i) early detection programs allow to diagnose early forms of melanoma as well as other skin tumors and are highly recommended; (ii) skin examination is recomended for people over 50 and for persons belonging to the risk groups; (iii) self control of the skin and surgical resection of suspected nevi is highly advised.